Antecedents and effects of empowering leadership: A regional approach to disengagement and innovation - Irwan, Andi; Budi, Rosdinaman; Zaitun, Cakra; Asrianto, Asrianto; Azizurrohman, Muhammad (Asian Management and Business Review, 2025)
This study investigates how psychological safety and transformational leadership influence empowering leadership and, in turn, how empowering leadership fosters job satisfaction to reduce employee disengagement and promote innovative work behavior. Drawing on self-determination theory and social exchange theory, this research develops an integrated model in which job satisfaction and empowering leadership serve as key mediators. Furthermore, the study examines the moderating role of regional context, urban versus regional areas in Indonesia, in shaping the relationship between job satisfaction and disengagement. Data were collected from 500 employees across various industries using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both psychological safety and transformational leadership significantly enhance empowering leadership, which subsequently boosts job satisfaction. In turn, job satisfaction reduces disengagement and indirectly promotes innovative work behavior. Importantly, the negative effect of job satisfaction on disengagement is significantly weaker in urban areas than in regional areas. This study contributes to leadership and organizational behavior literature by highlighting the contextual importance of region in disengagement dynamics. It offers practical insights for managers seeking to cultivate innovation through empowerment and regional sensitivity.